PERAN TEKNOLOGI INFORMASI DALAM AKTIFITAS DAKWAH: Menelusuri Signifikansi Dakwah Online - Rusli Rusli (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2013)
This paper deals with the role of information technology in da'wa acivities. It concludes that because of the spread of Internet, online da'wa as a kind of new model of Islamic preaching emerges. This kind of da'wa focused on the socialization that includes process of al-ta'aruf (acquaintance) and al-ta'aluf (harmony) with the target of object of Islamic preaching ( al-mad' u). This is carried out based on the three levels of online interaction, which includes spreading, participation and mobilization.